This Indian kid : a Native American memoir - Chuculate, Eddie, 1978- (Scholastic Focus, an imprint of Scholastic Inc., Publishers, 2023)
"Award-winning author Eddie Chuculate recounts his experience growing up in rural Oklahoma, from boyhood to young manhood, in an evocative and vivid voice. "Granny was full-blooded Creek, but the Bureau of Indian Affairs insisted she was thirteen-sixteenths. She showed her card to me. I'd sit at the kitchen table and stare at her when she was eating, wondering how you could be thirteen-sixteenths of anything and if so, what part of her constituted the other three-sixteenths." Growing up impoverished and shuttled between different households, it seemed life was bound to take a certain path for Eddie Chuculate. Despite the challenges he faced, his upbringing was rich with love and bountiful lessons from his Creek and Cherokee heritage, deep-rooted traditions he embraced even as he learned to live within the culture of white, small-town America that dominated his migratory childhood. Award-winning author Eddie Chuculate brings his childhood to life with spare, unflinching prose. This book is at once a love letter to his Native American roots and an inspiring and essential message for young readers everywhere, who are coming of age in an era when conversations about acceptance and empathy, love and perspective are more necessary than ever before."--